Urban inequality a case of public housing estates in Niger state, Nigeria - Iyanda, Sule Abass; Mohit, Mohammad Abdul (2015)

(untitled)
The vision of any housing policy is to provide liveable housing be it for the high, middle or low-income groups that are always underserved in terms of basic amenities. In the 21st century, the nature of living conditions in most of the public housing estates in Nigeria and Niger state in particular seems to be not any better off. The quality of living places, or cities, neighbourhoods or housing estates are linked with their physical environment, safety, social cohesion and infrastructure provided in the area. Studying the residential neighbourhood quality of public housing estates, the people living there are important. People living in a particular place receive direct effects from the changes of environment and development in their area. They know whether their housing environment status is either good or bad or change from time to time. Housing encompasses all that is necessary to make a living in a particular place pleasurable, and not a burden. It is however seen as an extension of the human frame that should respond to the needs of its inhabitants. Thus, housing serves as one of the best indicators of a person’s standard of living. Considering the above, satisfaction with housing neighbourhood environment indicates an environment that meets the needs and aspirations of the users and dissatisfaction means the needs and aspirations of the users were not met. No housing programme or policy can be considered successful only in terms of quantity constructed. Equally as important are the suitability of the residential environment, facilities and services to the users. Therefore, this study examined neighbourhood living conditions in three public low-income housing estates using data derived from household survey involving 366 respondents out of 400 questionnaires distributed based on stratified proportional sampling technique. The structured questionnaires were distributed face-to-face and collected back after completion either immediately or the following day. The data sought through questionnaires include different dimensions and indicators of good neighbourhood quality (liveability) as elicited from the literature review. Based on desktop literature, the study used both subjective and objective measurements to investigate the liveability of the selected housing estates. Issues examined include the home environment, neighbourhood amenities, economic vitality, social environment and civic protection. The data analysis techniques used include descriptive statistics, factor analysis and structural equation modelling (SEM). The outcome of the perception of residents’ in these selected housing estates can give a clue to the quality of the environment and serves as a feedback to be injected to housing policy for future development. Further, it could be used as an improvement tool as the study reveals the situation of the estates investigated.